PROBLEMS AND SOLUTIONS OF FURTHER DEVELOPMENT OF PHYSICAL EDUCATION IN THE PROCESS OF GLOBALIZATION - Akhmedov, Furkat (Журнал иностранных языков и лингвистики, 2023)
This article aims to provide analytical scientific information on the process of globalization and its consequences, the necessity and importance of physical education in the process.